An examination of data science’s application to the subject of energy management - Tiwari, Nachiket; Mishra, Paritosh; Pattanayak, Prem Ranjan; Chaudhary, Akshay; Jain, Samyak (AIP conference proceedings, 2024)
Due to HVAC systems, residential and commercial building energy consumption has constantly increased. Energy loads, transportation, storage, and user behavior affect building energy use. Technology can now precisely monitor, gather, and store this process’s massive data. This technology can meaningfully analyse and use such data. Data science to improve energy efficiency is a hot topic right now. This article discusses how energy management practitioners, particularly in the construction industry, have used data science to solve their most complex challenges. The paper also talks about the pros and cons of fully connected devices and new computer technologies.